DEVELOPMENT OF FOCUSKY BASED LEARNING MEDIA TO ENHANCE STUDENTS' CRITICAL THINKING SKILLS - Sedyati, Retna Ngesti; Triyanto, Jefri Rieski; Mujib, Muhammad Asyroful; Tiara; Wijayanti, Agustina Tri (Jurnal Pendidikan Ilmu Sosial, 2025)
The method used in this research is development research or Research and Development (R&D) adapted and modified from Branch's ADDIE Model, which consists of five steps. This study aims to (1) describe the process of developing Focusky learning media for the subject of business entities in the Indonesian economy and (2) evaluate how well the media improves the critical thinking skills of high school students. The uniqueness of this study lies in the integration of Focusky a tool rarely explored in economics education with a structured instructional design to encourage critical thinking. In this study, questionnaires and observations were used as data collection methods. Eleventh-grade IPS students at SMAN Pakusari will be the subjects of the study for the product effectiveness test, which will be conducted using effect size calculations and the Paired Sample T-Test. IBM SPSS 29 is used to assist with data analysis in this research. The results show that the integration of Focusky media significantly supports the development of students' critical thinking. Through engaging visual content and interactive features, this media facilitates deeper understanding and active learning. These findings emphasize the potential of technology-based learning tools to enrich classroom experiences and promote essential 21st-century skills in economic education. From the results of the statistical research, it shows that the Focusky learning media is effective in improving students' critical thinking skills based on the significance values of the pretest and posttest from the small group (0.046 < 0.05) and the large group (0.049 < 0.05). The effect size test results for the small group received a value of 0.79 and for the large group received a value of 0.80. Both values indicate that the developed Focusky media has a significant impact on enhancing students'critical thinking.